Exploring the Challenges of Initial Teacher Preparation: Voicing the Concerns from the Field - Fekede Tuli; Temesgen Oljira (RIRAI Publisher, 2020)
It is widely recognized that the best education systems have the best teachers, and a school can only ever be as good as its teachers. However, the quality of a teaching force is dependent on the availability of good quality teacher education program. Hence, the purpose of this study was to explore the challenges of initial teacher preparation program from insiders’ perspectives. Data were collected via semi-structured interview and analyzed narratively. The findings of the study revealed that failure to attract the right people into teaching, poor quality of teacher training programs, weak University and School partnership, unfair and disproportionate treatment of teacher education, policy- practice gap, poor teacher retention strategy, and poor information and communication technology integration as the challenges undermining the teacher education program. The need to attracting best and brightest candidates into the profession, strengthening teacher education programs, improving the management of teacher education, valuing teachers and improving their status are areas identified as implication of the study.